G366 Mapping research on the management of children and adults with down's syndrome: A systematic review of UK and ROI research and published outputs 1990–2015. (27th April 2016) - Manikam, L; Lee, R; Shafi, T; Venekamp, R; Schilder, A; McKenna, C; Littlejohns, P; Hayward, A; Lakhanpaul, M
Abstract : Down's Syndrome (DS) is one of UK's commonest genetic conditions with a stable incidence of 1 in 1000 live births. Despite this, there is a paucity of research on the most cost-effective management options. A systematic review was undertaken to map original UK and ROI research and identify gaps. In a follow-on study, we will undertake a prioritisation exercise involving experts, stakeholders and carers to prioritise future research investment. A systematic review of Medline, Embase, Cinahl-Ovid and Cochrane Library was undertaken utilising terms related to DS, UK and ROI. Exclusion criteria: (a) <10 patients, (b) publication date <1990 or (c) prenatal studies. Studies were categorised by participant demographics, study type, research and clinical themes, funding amount and type. Grey literature searches (Google Scholar), research networks (eg. Trisomy 21 Research Society, Down's Syndrome Medical Interest Group), charities (eg. Down Syndrome Association) are ongoing and will be reported at the conference. 2331 published articles were retrieved from electronic database searches. We excluded 2174 studies after screening titles/abstracts of which 80% were prenatal studies. After reviewing full text of the remaining 157 articles, a further 26 were excluded. This left 131 studies (Figure 1 ). A large number of articles (58; 44%) focused on disease epidemiology (eg. incidence, prevalence) with little studies undertaken (8; 6%) to improve their management. Data extraction is ongoing with further findings reported at the conference. With incidence remaining static and DS continuing to be a high-burden condition in the UK, DS should be an area of high priority for funders, policymakers and researchers. Once completed, this review will provide an insight into funding trends and research gaps in this vulnerable population. This will facilitate subsequent identification and prioritisation of research investments and priorities.